Perlindungan Hukum Terhadap Nasabah dalam Perjanjian Kredit Ditinjau dari Undang-Undang Nomor 10 Tahun 1998 Tentang Perbankan - Gresdiana Enjelica Goreti; Darius Mauritsius; Chatryen M. Dju Bire (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
A credit agreement is a legal framework that quides interaction beetwen banking institutions and their cliens regarding banking services. However the implementation of such agreements can raise various legal challenges, particulary if there are irregularities during the credit approval stage. One example is the falsification of credit documents, which has the potential to cause financial losses for both the bank and its clients. This study examines the legal protection provided for customers in loan contracts and examines the legal responsibilities arising from falsification of credit documents at the Maumere Branch of BRI Bank. This study adopted a normative legal method enriched with legal and conceptual reviews. This study utilized primary, secondary, and tertiary legal sources and analyzed qualitatively. The results indicate that customer protection is regulated by law number 10 of 1998 concerning banking. Which reguires banks to conduct their operations by prioritizing the principle of prudence. However, the partice of document falsification indicates shortcomings in the internal oversight system and suboptimal implementation of prudential standars. Therefore, improving internal oversight and fostering the integrity of bank employees is cricual to ensure adequate costumer protection and maintain public confidence in banking institutions.